Electronic Energy Transfer and Quantum-Coherence in π-Conjugated Polymers - Hwang, Inchan; Scholes, Gregory D (Chemistry of materials, 2011)
Electronic energy transfer (EET) has been the subject of intense research because of its significant contribution to the photophysical properties of various material systems. For π-conjugated polymers, it has long been accepted that a classical hopping mechanism is dominant in the energy transfer dynamics because of a weak electronic coupling. However, recent research reveals that conjugated polymers, in fact, can have an electronic coupling strong enough to preserve quantum-coherence. In this review, we summarize the main photophysical features of conjugated polymers. We discuss how electronic excited states evolve on various time scales from femtoseconds to hundreds of picoseconds in terms of exciton relaxation, localization, and electronic energy transfer. The Förster energy transfer model and modifications needed for describing energy transfer in conjugated polymers are described. We discuss how chain conformation and its disorder influence EET and the time scale of the evolution of electronic excited states, and demonstrate how quantum coherence contributes to energy transfer dynamics. Recent research on exciton diffusion in various kinds of polymers is summarized.